Editoral: From Local Budgeting to Green Policy (Emerging Issues in Indonesian Public Administration and Governance) - khayu rohmi; Tissa Silvia; Rizky Amalia Putri (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2026)
The public sector in Indonesia stands at a critical juncture, shaped by a confluence of historical legacies, ongoing reforms, and the pressing demands of a rapidly evolving society. The urgency to understand and address the dynamics of governance, policy implementation, and public service delivery in Indonesia is underscored by the nation’s commitment to citizen welfare, equitable development, and the realization of good governance principles. As the world’s fourth most populous country and a diverse archipelago, Indonesia’s public sector faces unique challenges and opportunities that make its transformation both urgent and complex.